Civil liability of electricity companies arising from electrocution cases - Albala'wi, Dr. Nasir (The journal of contemporary issues in business and government, 2021)
The aim of this study is to identify the basis of civil liability arising from the electrocution of electricity companies as guardians of their electrical installations, which are among the things that require special attention according to the Jordanian Civil Law. A distinction is made between responsibility for personal action, responsibility for things and the burden of proving responsibility. There are many and many cases of stunting, and the forms of error and the responsibility are also mixed. Whereas, the Jordanian legislator did not deal with this case and left it to the general rules, which makes it difficult to deduce its elements. Therefore, the study found that the Jordanian legislator established responsibility for the personal act on the basis of the damages, and did not base it on the fault. And that the Jordanian judiciary took the principle of actual guarding of something and not the principle of legal guarding. The study recommended the necessity of individuals with special provisions dealing with the civil liability of things with the General Electricity Law and amending the provisions of the Jordanian Civil Law to include a special standard to distinguish between responsibility for personal action and responsibility for things.